Aquatic macroinvertebrate monitoring report - Vinson, Mark R.; Utah State University. Dept. of Fisheries and Wildlife ([Utah State University. Dept. of Fisheries and Wildlife], 1999)
A 13.66/2: Aq2x 106 Cover title.; "16 April 1999."; Includes bibliographical references. Samples were taken from Beaver Creek, East Fork of Ashland Creek, Glade Creek, Little Applegate River, McDonald Creek, Neil Creek, Palmer Creek, North and South Forks of Little Butte Creek, and Yale Creek, Jackson County, Oregon. "Samples were identified at the BLM Aquatic Ecosystem Laboratory in Logan, Utah . Benthic macroinvertebrates are important elements of water quality evaluations because they (1) live in, on, or near streambed sediments; (2) have relatively long life cycles; and (3) are relatively sessile compared with larger organisms, such as fish. This combination of characteristics ensures that benthic invertebrates (1) respond to natural and anthropogenic environmental conditions that physical or chemically alter streambed sediments; (2) integrate effects over a year; and (3) characterize effects over a relatively small spatial scale (in contrast with fish, which may travel long distances). These factors make benthic invertebrates well suited for use in assessing site-specific water quality and comparing spatial patterns of water quality at multiple sites, and for integrating effects up to a year after a pollution or disturbance event. The distribution of benthic invertebrates in a stream is a response to natural and anthropogenic influences" P. v,1 [5,6].